2016
DOI: 10.1155/2016/1850401
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Consequences of the Elastic Properties of Dental Implant Alloys on the Supporting Bone: Finite Element Analysis

Abstract: The objective of the present study is to evaluate how the elastic properties of the fabrication material of dental implants influence peri-implant bone load transfer in terms of the magnitude and distribution of stress and deformation. A three-dimensional (3D) finite element analysis was performed; the model used was a section of mandibular bone with a single implant containing a cemented ceramic-metal crown on a titanium abutment. The following three alloys were compared: rigid (Y-TZP), conventional (Ti-6Al-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…[21,22] A recent FEA implant model study pointed out a phenomenon that zirconia received higher stress value compared to titanium. [42] The authors further suggested that there may be a direct relationship between Young's modulus of the material and the stress transferred to the implant, that a more rigid implant absorbs more stress. [42] This may partly explain why in our study, there was less stress in the peri-implant bone in the Zir implant compared to the Ti implant.…”
Section: Discussionmentioning
confidence: 99%
“…[21,22] A recent FEA implant model study pointed out a phenomenon that zirconia received higher stress value compared to titanium. [42] The authors further suggested that there may be a direct relationship between Young's modulus of the material and the stress transferred to the implant, that a more rigid implant absorbs more stress. [42] This may partly explain why in our study, there was less stress in the peri-implant bone in the Zir implant compared to the Ti implant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the better biomechanical behaviour of a more rigid, high elasticity modulus implant seems to exist when it is surrounded by cortical bone with similar elastic properties. However, for a less rigid trabecular bone, we found better biomechanical behaviour when an implant manufactured employing a lower elastic modulus alloy is used [ 13 , 14 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to evaluate the biomechanical properties of implants with low Young's moduli. However, it has been reported that a low elastic modulus of the implant material results in greater cortical and trabecular bone deformation 38) . In this model, it was assumed that the bone had linear elastic properties to evaluate the stress distribution transferred from an implant with a low elastic modulus to the supporting bone.…”
Section: Discussionmentioning
confidence: 99%